Sleep in times of crises: A scoping review in the early days of the COVID-19 crisis. (December 2021) - Simonelli, Guido; Petit, Dominique; Delage, Julia Pizzamiglio; Michaud, Xavier; Lavoie, Marie Denise; Morin, Charles M.; Godbout, Roger; Robillard, Rebecca; Vallières, Annie; Carrier, Julie; Bastien, Célyne
Summary: During the early days of the pandemic and in the context of a seemingly unknown global threat, several potential major sleep disruptors were identified by sleep researchers and practitioners across the globe. The COVID-19 pandemic combined several features that, individually, had been shown to negatively affect sleep health in the general population. Those features included state of crisis, restrictions on in-person social interactions, as well as financial adversity. To address the lack of a comprehensive summary of sleep research across these three distinctive domains, we undertook three parallel systematic reviews based on the following themes: 1) Sleep in times of crises; 2) Sleep and social isolation; and 3) Sleep and economic uncertainty. Using a scoping review framework, we systematically identified and summarized findings from these three separated bodies of works. Potential moderating factors such as age, sex, ethnicity, socioeconomic status, psychological predisposition, occupation and other personal circumstances are also discussed. To conclude, we propose novel lines of research necessary to alleviate the short- and long-term impacts of the COVID-19 crises and highlight the need to prepare the deployment of sleep solutions in future crises.